1995
DOI: 10.1111/j.1365-2427.1995.tb01156.x
|View full text |Cite
|
Sign up to set email alerts
|

The stream as a habitat templet for bryophytes: species' distributions along gradients in disturbance and substratum heterogeneity

Abstract: 1. The structure of bryophyte communities in streams in relation to habitat characteristics,, especially disturbance, is described. Disturbance in rivers is quantified as movement of the stream bed, whereas in small streams water level fluctuation is used as an indicator of disturbance frequency. 2. Canonical correspondence analysis differentiated frequently disturbed sites from more stable ones. The existence of a disturbance gradient was confirmed in a subset of the study sites using long-term records of dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
132
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(145 citation statements)
references
References 50 publications
11
132
2
Order By: Relevance
“…Harsh, homogenous traits Habitat harshness as trait filter (Thienemann, 1918) Temporal heterogeneity = disturbance/stress Running water predictions (Southwood, 1977) Spatial heterogeneity = provision of refugia stream bryophytes (Muotka & Virtanen, 1995), stream and lake hydrophytes (Willby, Abernethy & Demars, 2000;Demars & Harper, 2005), benthic pond invertebrates (Verberk, Siepel & Esselink, 2008), marine benthic invertebrates (Bremner, Rogers & Frid, 2003b) or fluvial floodplain plants and birds (Bournaud, 1994;Pautou & Arens, 1994). These theoretical studies also stimulated work on applied aspects of trait responses to human-caused stressors (or release from stress after restoration) of organisms such as benthic stream invertebrates DolĂ©dec et al, 1999), stream fish (Ferreira et al, 2007;Schmutz et al, 2007), benthic pond or lake invertebrates (Menetrey et al, 2005;Van Kleef et al, 2006), waterway hydrophytes (Willby, Pygott & Eaton, 2001), lagoon fish, benthic invertebrates, macrophytes and plankton (Mouillot et al, 2006;Pravoni, Da Ponte & Torricelli, 2008), marine benthic invertebrates (Bremner, Frid & Rogers, 2003a;Frid et al, 2008), marine fish (Jennings, Greenstreet & Reynolds, 1999), fluvial floodplain plants, molluscs and insects (Dziock, 2006;Foeckler et al, 2006;Henle et al, 2006) or forest birds (Hausner, Yoccoz & Ims, 2003).…”
Section: Benign Heterogenous Traitsmentioning
confidence: 99%
“…Harsh, homogenous traits Habitat harshness as trait filter (Thienemann, 1918) Temporal heterogeneity = disturbance/stress Running water predictions (Southwood, 1977) Spatial heterogeneity = provision of refugia stream bryophytes (Muotka & Virtanen, 1995), stream and lake hydrophytes (Willby, Abernethy & Demars, 2000;Demars & Harper, 2005), benthic pond invertebrates (Verberk, Siepel & Esselink, 2008), marine benthic invertebrates (Bremner, Rogers & Frid, 2003b) or fluvial floodplain plants and birds (Bournaud, 1994;Pautou & Arens, 1994). These theoretical studies also stimulated work on applied aspects of trait responses to human-caused stressors (or release from stress after restoration) of organisms such as benthic stream invertebrates DolĂ©dec et al, 1999), stream fish (Ferreira et al, 2007;Schmutz et al, 2007), benthic pond or lake invertebrates (Menetrey et al, 2005;Van Kleef et al, 2006), waterway hydrophytes (Willby, Pygott & Eaton, 2001), lagoon fish, benthic invertebrates, macrophytes and plankton (Mouillot et al, 2006;Pravoni, Da Ponte & Torricelli, 2008), marine benthic invertebrates (Bremner, Frid & Rogers, 2003a;Frid et al, 2008), marine fish (Jennings, Greenstreet & Reynolds, 1999), fluvial floodplain plants, molluscs and insects (Dziock, 2006;Foeckler et al, 2006;Henle et al, 2006) or forest birds (Hausner, Yoccoz & Ims, 2003).…”
Section: Benign Heterogenous Traitsmentioning
confidence: 99%
“…Logs provide habitat for many species of bryophytes, and different decay classes and sizes of logs support different communities Table 5. of bryophytes (Gustafsson and HallingbĂ€ck 1988;Söderström 1988a). Disturbing these habitats can reduce bryophyte diversity dramatically (Muotka and Virtanen 1995).…”
Section: Why Are Old-growth Forests Rich With Bryophytes?mentioning
confidence: 99%
“…The results of such research indicate the importance of substrates and habitats. Habitats such as streams, fens, and bogs exhibit unique patterns of bryophyte diversity (Slack and Glime 1985;Muotka and Virtanen 1995;. Vitt and Belland (1997) have shown that patterns of bryophyte diversity are strongly correlated to habitat type and scale of the investigation.…”
Section: Introductionmentioning
confidence: 99%
“…For a description of the sampling methods, refer to Muotka and Virtanen (1995). Environmental variables of importance to bryophytes include habitat structure and water chemistry.…”
mentioning
confidence: 99%